Hyperpolarized 3He Functional Magnetic Resonance Imaging of Bronchoscopic Airway Bypass in Chronic Obstructive Pulmonary Disease - Lindsay Mathew; Miranda Kirby; Donald Farquhar; Christopher Licskai; Giles Santyr; Roya Etemad-Rezai; Grace Parraga; David G McCormack (Canadian Respiratory Journal)
A 73-year-old exsmoker with Global initiative for chronic Obstructive Lung Disease stage III chronic obstructive pulmonary disease underwent airway bypass (AB) as part of the Exhale Airway Stents for Emphysema (EASE) trial, and was the only EASE subject to undergo hyperpolarized 3He magnetic resonance imaging for evaluation of lung function pre- and post-AB. 3He magnetic resonance imaging was acquired twice previously (32 and eight months pre-AB) and twice post-AB (six and 12 months post-AB). Six months post-AB, his increase in forced vital capacity was <12% predicted, and he was classified as an AB nonresponder. However, post-AB, he also demonstrated improvements in quality of life scores, 6 min walk distance and improvements in 3He gas distribution in the regions of stent placement. Given the complex relationship between well-established pulmonary function and quality of life measurements, the present case provides evidence of the value-added information functional imaging may provide in chronic obstructive pulmonary disease interventional studies.